Spice gardens in web-based experiential tourism: A study from Matale Divisional Secretariat Division, Sri Lanka - Delpearachchi, D.A.L.H.; Dunsford, L.B.; Gajanayaka, K.G.M.C.P.B.; Pathirathna, L.P.S.S. (Colombo Economic Journal, 2023)
With the digitalization of the tourism sector, many hosts and guests use digital platforms to conduct their businesses and travel worldwide. Web-based experiential tourism is an emerging platform where people can visit places virtually, enabling people to share knowledge and experience worldwide while earning an income. Sri Lanka is a popular tourist destination for spice tourism and is ideal for most of the world’s spice crops. The Sri Lankan tourism industry was restricted to physical interactions and was hardly available on online platforms. This study examined the potential of ‘web-based experiential tourism’ for spice gardens in the Matale divisional secretariat division. Primary data was collected from 23 spice gardens to review the potential Web-based experiential activities. Twenty tour guides from the Matale district were interviewed to determine tourists’ willingness to engage in available spice garden activities. Thereby, the ‘Tourists Preference Index’ (TPI) was developed. The results identified five activities with the highest tourist preference. Secondary data was collected from ‘Airbnb’ listings. The data was descriptively analyzed to introduce the possibility of monetizing spice garden activities as web-based experiential tourism.
Keywords: Airbnb; Experiential tourism; Monetizing; Spice gardens; Tourist Preference Index; Web-based